Correction: Assessing the Evidence for Asymmetrical Switch Costs and Reversed Language Dominance Effects – A Meta-Analysis. Issue 1 (10th November 2021) - Gade, Miriam; Declerck, Mathieu; Philipp, Andrea M.; Rey-Mermet, Alodie; Koch, Iring
This article details a correction to: Gade, M., Declerck, M., Philipp, A. M., Rey-Mermet, A., & Koch, I. (2021 ). Assessing the Evidence for Asymmetrical Switch Costs and Reversed Language Dominance Effects – A Meta-Analysis. Journal of Cognition, 4 (1), 55. DOI: http://doi.org/10.5334/joc.186